Optimizing planting geometries in eucalyptus-based food production systems for enhanced yield and carbon sequestration - Chavan, S. B.; Dhillon, R. S.; Sirohi, Chhavi; Saleh, Ibrahim A.; Uthappa, A. R.; Keerthika, A.; Jinger, Dinesh; Halli, Hanamant M.; Pradhan, Aliza; Kakade, Vijaysinha; Morade, Amrut; Chichaghare, A. R.; et al. (Frontiers in Sustainable Food Systems, 2024)
The integration of trees into diverse land use systems holds potential for India to meet nationally determined contribution (NDC) targets under the Paris Climate Agreement. With a target of sequestering 2.5 to 3 billion tons of CO2 equivalent by 2030, the study focused on the widespread and economically viable eucalyptus-based agroforestry, practiced widely in various planting geometries tailored to meet industrial end-use requirements. In this context, a detailed study was conducted to quantify the influence of five planting geometries of eucalyptus on intercrops (Dhaincha - barley rotation) biomass, soil properties, and carbon stock of the system during 2009-2016. Results revealed that biomass accumulation of different tree components was 62.50–74.09% in stem; 6.59–9.14 % in branch; 3.18–5.73% in leaves; 12.20–20.44% and 1.71–3.48% in fine roots across the planting geometries. The mean carbon content of stem, branch, leaves and roots was 49.00, 47.00, 43.00 and 49.00 %, respectively. Over the 8–years period, geometry of 3×3 m performed better in terms of total biomass production (344.60 Mg ha− 1 by tree biomass and 62.53 Mg ha−1 by intercrops). The tree diameter at breast height and height (DBH2H) was found as a very good predictor of dry weight followed by DBH alone. Among various functions (linear, allometric, logistic, Gompertz, Chapman and exponential), the best-fit equation was allometric i.e. B=300.96*DBH2H0.93 (Adj R2- 0.96) for eucalyptus based on universal model adequacy and validation criteria. The carbon sequestration rate was maximum (20.79 Mg C ha–1 yr–1) in 3×3 m followed by 17×1×1 m. The total carbon stock of eucalypts–based system (tree+crop+soil) varied significantly under different planting geometries and sole crop rotation (dhaincha–barley). The higher carbon storage (237.27 Mg ha–1) obtained from 3×3 m spacing and further partitioning carbon stock in tree—166.29 Mg ha–1, crop—25.01 Mg ha–1 and soil—45.97 Mg ha–1. Tree-based systems were valuable components of agriculture, advocating for their widespread adoption to reduce CO2 emissions and generate income through carbon credits. These findings will provide crucial insights of sustainable land use practices and advance India’s commitment towards adaptation of climate change mitigation strategies.